ROLE OF NEUROPEPTIDE GALANIN IN THE PATHOGENESIS OF TYPE 2 DIABETES MELLITUS - Dr. Rohit Kumar Mishra; Dr. Stuti Singh; Dr. Palash Ratna; Dr. Sanjay Khattri; Dr. Richa Mishra (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Introduction: In this study, the characteristic milestones of type 2 diabetes mellitus were condensed as two analogical models, insulin resistance-type 2 diabetes mellitus and galanin resistance-type 2 diabetes mellitus. Galanin resistance and insulin resistance should be related to each other. Obesity and BMR along with other factors which are components of syndrome X should have a relation to both insulin resistance and galanin resistance.Aim & Objective: Aim is to determine the accuracy of circulating galanin for early prediction of Type 2 Diabetes Mellitus. Objective is to assess the comparative serum level of galanin in patients with type-2 diabetes mellitus and healthy controls along with the correlation of serum galanin level with Insulin Resistance & the risk factors of type-2 diabetes mellitus.Material & Method: This study was conducted in the Department of Pharmacology & Therapeutics at King George’s Medical University (KGMU), Lucknow. Patients registered in OPD of the Department of Medicine, King George’s Medical University, Lucknow who were diagnosed to be the cases of T2DM were screened based on selection criteria for the study. Controls were screened among healthy men and women between 18-60 years of age who have not been diagnosed with any physical or psychological illness for which they are not on any kind of regular medication. A total of 50 healthy individuals of similar ethnicity from North India were recruited as controls. 50 selected cases as well as controls were subsequently called for sample collection on the next day in a fasting state.Result: This study shows that the level of serum galanin is significantly higher in Type-2 Diabetes Mellitus patients as compared to healthy controls in the North Indian population. The Body Mass Index, Waist-to-Hip ratio, Systolic Blood Pressure, Diastolic Blood Pressure, Fasting Blood Sugar, Total Cholesterol, Triglycerides, and LDL-C are significantly higher in type-2 diabetic mellitus patients as compared to healthy controls. The level of HDL-C is higher in healthy controls than in Type-2 Diabetes patients. Fasting Insulin level and Insulin resistance index (HOMA-IR) was found to be significantly higher in Type-2 Diabetes patients as compared to healthy controls. Pancreatic β-cell index (HOMA-B) levels of healthy controls were found to be significantly higher than that of Type-2 Diabetic patients. A strong positive correlation of Galanin was observed with Weight, BMI, Triglyceride levels, Insulin and HOMA-IR levels. A moderate correlation of Galanin was observed with Fasting Blood Sugar and HbA1C. Galanin did not show any correlation with age and LDL levels of the study population.Conclusion: An optimum cut-off value for serum Galanin above 19.135 pg/ml is predictive of Type-2 Diabetes Mellitus with 86.0% Sensitivity and 78.0% Specificity.